Giant 2D Skyrmion Topological Hall Effect with Ultrawide Temperature Window and Low-Current Manipulation in 2D Room-Temperature Ferromagnetic Crystals - Zhang, Gaojie; Luo, Qingyuan; Wen, Xiaokun; Wu, Hao; Yang, Li; Jin, Wen; Li, Luji; Zhang, Jia; Zhang, Wenfeng; Shu, Haibo; Chang, Haixin (Chinese physics letters, 2023)
The discovery and manipulation of topological Hall effect (THE), an abnormal magnetoelectric response mostly related to the Dzyaloshinskii–Moriya interaction (DMI), are promising for next-generation spintronic devices based on topological spin textures such as magnetic skyrmions. However, most skyrmions and THE are stabilized in a narrow temperature window either below or over room temperature with high critical current manipulation. It is still elusive and challenging to achieve large THE with both wide temperature window till room temperature and low critical current manipulation. Here, using controllable, naturally oxidized sub-20 and sub-10 nm 2D van der Waals room-temperature ferromagnetic Fe 3 GaTe 2− x crystals, we report robust 2D skyrmion THE with ultrawide temperature window ranging in three orders of magnitude from 2 to 300 K, in combination with giant THE of ∼ 5.4 μΩ⋅cm at 10 K and ∼ 0.15 μΩ⋅cm at 300 K, which is 1–3 orders of magnitude larger than that of all known room-temperature 2D skyrmion systems. Moreover, room-temperature current-controlled THE is also realized with a low critical current density of ∼ 6.2 × 10 5 A⋅cm −2 . First-principles calculations unveil natural oxidation-induced highly enhanced 2D interfacial DMI reasonable for robust giant THE. This work paves the way to room-temperature electrically controlled 2D THE-based practical spintronic devices.